Student entrepreneurship: a bibliometric analysis - Cucino, Valentina; Passarelli, Mariacarmela; Bongiorno, Giuseppe; Piccaluga, Andrea; Cariola, Alfio (Piccola Impresa / Small Business, 2022)
The present paper aims to investigate the literature on student entrepreneurship in order to identify the most recent research field. The approach used in this study is the bibliometric analysis of secondary data allows generating useful information to investigate both current research trends and future research trends (Rey-Martí et al., 2016). The analysis of Co-Citation identifies consolidated trends in the literature: the behavioral planned theory, the educational paths and some demographic trajectories. The coupling analysis get new trends and future research trends. Recent studies focus on a new emerging factor that is “entrepreneurial intention of students”. Then, others focus on the effect of some micro factors (personal attitudes, psychological factors, etc.) and macro factors (ecosystem’s characteristics) on the student entrepreneurial intention. This represents one of the first studies to apply bibliometric analysis to the topic of student entrepreneurship